The Impact of Adoption of XBRL on Information Risk in Representative Countries of Scandinavian Region - Valentina Tohang; Michellen Lan (Jurnal Keuangan dan Perbankan, 2017)
This study aimed to examine the impact of the adoption of eXtensible Business Reporting Language (XBRL) in reduced the information risk of financial reporting disclosures. Information transparency, information asymmetry, the efficiency of the information and also the quality of the information disclosures will impact upon information risk. An increased of information risk and information asymmetry will reduce transparency and efficiency of the financial disclosures due to the unqualified financial and non-financial information provided by the companies (Kim, Kim, No, 2011). Event return volatility (ERV) used to represent the occurrence of information risk. Used a sample of listed companies in the Scandinavian region of the European Union (EU), we found that XBRL adoption had lowered the occurrence of information risk. This finding supported by prior studies which stated, that a decrease in the degree of ERV, as a proxy of lower information risk, may directly impact the information quality, information efficiency, and information transparency. By detected the existence of information risk, stakeholders can more aware of the necessity to ensured the quality of the reporting information disclosure. This paper also highlighted the benefits of adopting XBRL as a reporting standard to improved the company’s reporting disclosure.DOI: https://doi.org/10.26905/jkdp.v21i4.1525